Prevalence, Knowledge, Practice and Perception of Self Medication among Pharmacy Students in a Nigerian tertiary Institution - Mgbahurike A. A.; Nenwi G. F (Journal of Medical Biomedical and Applied Sciences, 2020)
The practice of self-medication has become a form of self-care and is a global trend that is encouraged when it deals with minor illnesses and with proper guide and information. In countries where there are no strict regulations and prescription drugs are freely dispensed, irresponsible self-medication is common. This study aimed to assess the prevalence, knowledge, practice and perception of self-medication among pharmacy students in University of Port Harcourt. The study included all pharmacy students from 200L to 500L who gave their consent to participate. Ethical approval was obtained from the University Ethics and Research Committee. Descriptive cross sectional study design was adopted. Pre-tested structured questionnaire was used to collect the required data. The questionnaire was structured in four parts: demographic; knowledge; practice and perception sections.A total of 476 pharmacy students responded and gave their consent to the study. 42.4% (202) were male and 57.6% (274) were female. The mean age of the population was 24.55±5.32years. Most of the respondents, 49.2% (234), were within the age of 20 – 25years, while 4.4% (21) were more than 30years. Most, 94.7% (451) were single. 37% were in 200L, 22.9% (109) in 400L, and 18.9% (90) in 500L. Prevalence rate of self-medication among these students was 83.8%. A significant (p>0.05) percentage, 69.8% (327) showed good knowledge of self-medication and agreed to the need to consult health professional before consuming medicines, and yet a good number, 51.4% (245) often practice self- medication. The most common source of information for their self-medication was textbooks/class materials, 31.1% (148). The respondents showed positive perception towards self- medication as many, 40.3% (192) claimed that self –medication is right /safe and should be encouraged. Knowledge about the medicine used (91.8%) (437)was the commonest reason for self –medication, while analgesic/antipyretic (91.6%) (436) was the commonest class of medicines used for self-medication. The next common class of medicine was antibiotics, (84.7%) (403) and herbal remedy was the least, 15.5% (74). Fever, 83.6% (398), headache 80.5% (383), were the most common ailment treated by self-medication. Dependence on textbooks/class materials as information source increases significantly (p>0.05) with increase in years of study. In conclusion self- medication is highly prevalent among the pharmacy students evaluated. There is need to steer these students towards responsible self- medication especially towards antibiotics stewardship.